Noncompaction myocardium in association with type Ib glycogen storage disease - Goeppert, Benjamin; Lindner, Martin; Vogel, Monika Nadja; Warth, Arne; Stenzinger, Albrecht; Renner, Marcus; Schnabel, Philipp Albert; Schirmacher, Peter; Autschbach, Frank; Weichert, Wilko (Pathology, research and practice, 2012)
Noncompaction myocardium is a rare disorder assumed to occur as an arrest of the compaction process during the normal development of the heart. Left ventricular noncompaction has been reported to be associated with a variety of cardiac and extracardiac, especially neuromuscular abnormalities. Moreover, it has been suggested that metabolic alterations could be responsible for the noncompaction. However, no association of noncompaction myocardium with type Ib glycogen storage disease (GSD) has been reported so far. Type Ib GSD is due to a defect of a transmembrane protein which results, similar to type Ia GSD, in hypoglycemia, a markedly enlarged liver and, additionally, in neutropenia, recurrent infections, and inflammatory bowel disease. Until now, no muscular or cardiac involvement has been described in type Ib GSD patients. The present case represents the first report of a noncompaction myocardium in a child with type Ib GSD who died of sudden clinical deterioration at the age of four.